Application of Geoelectrical Resistivity Imaging Technique for the Estimation of Soil Water in Universiti Putra Malaysia - Asry, Zeinab (2009)
This study describes the application of electrical resistivity imaging technique in the estimation of soil water in UPM, Selangor, Malaysia. Electrical Resistivity Imaging surveys have been conducted in order to locate, delineate subsurface water resources and estimate its reserve. The resistivity imaging surveys carried out basically measures and maps the resistivity of subsurface materials. A 2-D geoelectrical resistivity technique was used. Resistivity measurement was carried out using an ABEM SAS 4000 terrameter with electrode selector system. A Wenner electrode configuration was employed. The field survey was conducted along thirteen profiles providing continuous coverage. Colour-modulated sections of resistivity versus depth were plotted for all lines, giving an approximate image of the subsurface structure. The field survey was accompanied by laboratory work. Resistivity of soil samples and groundwater was measured and the resistivity formation ratio was obtained. The porosity and water saturation of the same samples were calculated. A relationship between the porosity and the resistivity formation ratio as well as water saturation was established. The laboratory established relationship between moisture content and resistivity; the porosity against resistivity formation ratio and resistivity formation ratio against water saturation were used to estimate the volume of soil water above the bedrock within the study area. The porosity values were contoured and plotted. Depth to the bedrock for each line was obtained. A 2-dimensional and 3- dimensional representation of the subsurface topography of the area was prepared using commercial computer software. The use of the software also enabled the computation of the amount of soil water above the bedrock within the area investigated. The results showed that the layers associated with the resistivities between 30